Low-temperature deposition manufacturing technology: a novel 3D printing method for bone scaffolds - Sun, Tianze; Wang, Jinzuo; Huang, Huagui; Liu, Xin; Zhang, Jing; Zhang, Wentao; Wang, Honghua; Li, Zhonghai (Frontiers in Bioengineering and Biotechnology, 2023)
The application of three-dimensional printing technology in the medical field has great potential for bone defect repair, especially personalized and biological repair. As a green manufacturing process that does not involve liquefication through heating, low-temperature deposition manufacturing (LDM) is a promising type of rapid prototyping manufacturing and has been widely used to fabricate scaffolds in bone tissue engineering. The scaffolds fabricated by LDM have a multi-scale controllable pore structure and interconnected micropores, which are beneficial for the repair of bone defects. At the same time, different types of cells or bioactive factor can be integrated into three-dimensional structural scaffolds through LDM. Herein, we introduced LDM technology and summarize its applications in bone tissue engineering. We divide the scaffolds into four categories according to the skeleton materials and discuss the performance and limitations of the scaffolds. The ideas presented in this review have prospects in the development and application of LDM scaffolds.